KOLABORASI PERPUSTAKAAN POLITEKNIK NEGERI BANDUNG DENGAN IGROUP SEBAGAI UPAYA MENINGKATKAN E-RESOURCES - Hanifatunnisa, Najwa Auliana; Rachmawati, Tine Silvana (VISI PUSTAKA: Buletin Jaringan Informasi Antar Perpustakaan, 2024)
The need for electronic reading resources is very high, considering their impact in supporting learning, research, and scientific development. Therefore, cooperation between libraries and e-resources publishers is one solution that can be realized, especially in higher education libraries. The purpose of the research is to find out (1) the process of cooperation between the Academic Support Unit of the Bandung State Polytechnic Library and iGroup in improving e-resources and to find out (2) the publishers of e-resources that the Academic Support Unit of the Bandung State Polytechnic Library subscribes to through this cooperation. The research was conducted using qualitative methods with data collection techniques in the form of literature studies and interviews and data analysis techniques consisting of data reduction, data presentation, and conclusion. The results showed that the cooperation process between the Academic Support Unit of the Bandung State Polytechnic Library and iGroup consisted of 6 stages, namely notification of information regarding the amount of funds, making then submitting the Work Plan and Budget of the Ministry of State / Institution to the Goods / Services Procurement Work Unit, auctioning, selecting partners, and making contracts. The results showed that the cooperation opened access for the Academic Support Unit of the Bandung State Polytechnic Library to subscribe to international publishers, namely SpringerLink and Emerald Insight. There are also other findings that the Academic Support Unit of the Bandung State Polytechnic Library has made several efforts in promoting e-resources that have been subscribed to the Bandung State Polytechnic academic community, both offline and online.